THE QUALITY OF SMART MOBILITY: A SYSTEMATIC REVIEW - Simon NAGY; Csaba CSISZÁR (Scientific Journal of Silesian University of Technology. Series Transport)
Smart cities and smart mobility are often analysed by systematic, sustainability-related, informatical, etc., issues. However, the quality elements of smart mobility services have not yet been reviewed. In this paper, we reviewed smart cities and smart mobility as well as the quality elements of smart mobility services. Based on the reviewed literature, we illustrated the requirements against smart mobility and uncovered the need for optimisation. We also interpret a monitoring method based on SERVQUAL. This method can be a base of establishing key performance indicators as well as benchmarking between cities.